1 | ÷ | 3 | × | ( | 2 | x | − | 1 | ) | − | ( | x | − | 2 | ) | ÷ | 6 | = | 1 |
Left side of the equation = | 1 3 | ( | 2 | x | − | 1 | ) | − | ( | x | − | 2 | ) | × | 1 6 |
1 3 | ( | 2 | x | − | 1 | ) | − | ( | x | − | 2 | ) | × | 1 6 | = | 1 |
Left side of the equation = | 1 3 | × | 2 | x | − | 1 3 | × | 1 | − | ( | x | − | 2 | ) | × | 1 6 |
= | 2 3 | x | − | 1 3 | − | ( | x | − | 2 | ) | × | 1 6 |
= | 2 3 | x | − | 1 3 | − | x | × | 1 6 | + | 2 | × | 1 6 |
= | 2 3 | x | − | 1 3 | − | x | × | 1 6 | + | 1 3 |
= | 1 2 | x | − | 0 |
1 2 | x | − | 0 | = | 1 |
x | = | 1 | ÷ | 1 2 |
= | 1 | × | 2 |
x | = | 2 |